Effect of hydrotherapy and yogic kriyas on snoring: A randomized control study - K J Sujatha; Shetty Prashant; Shenoy Deeksha; G S Pooja (Wolters Kluwer Medknow Publications, 2021)
Introduction: Snoring is a common sleep disorder, considered as a cardinal symptom of obstructive sleep apnea. The present study aims to explore and substantiate the clinical effect of hydrotherapy with Yogic Kriyas in individuals with snoring. Methods: Randomized control trial, where 60 patients aged 30-55 years were recruited and were randomly allocated into case and control groups. Subjects were assessed for systolic and diastolic blood pressure (SBP, DBP), respiratory rate (RR), pulse rate (PR), epworth sleepiness scale, Berlin and Short Form-36 (SF-36) questionnaires, weight, body mass index (BMI), saturation of peripheral oxygen (SpO2), and heart rate variability (HRV) before and after 10 days of intervention. Results: In case group, there was a significant increase in the values of SF-36 scoring (P = 0.0002), SPO2 (P = 0.002), Berlin score (P = 0.0001) and a significant decrease in weight (P = 0.0001), BMI (P = 0.0001), Epworth questionnaire score (P = 0.0001), SBP (P = 0.0008), DBP (P = 0.0001), PR (P = 0.0001), and RR (P = 0.00) following the intervention. In time domain of HRV, there was significant reduction in mean heart rate (P = 0.0001). In frequency domain, a significant increase was observed in high frequency (HF) value (P = 0.043) and a significant reduction was observed in low frequency (LF) (P = 0.0001) and LF/HF Ratio (P = 0.0005). In control group, significant reduction was seen in weight, BMI (P = 0.0001), PR (P = 0.0001) and RR (P = 0.0001). Conclusion: Naturopathy intervention with Neutral throat pack, Neutral chest pack, Yogic Neti kriyas, Steam inhalation reduces sympathetic tone and shifts the sympathovagal balance in favor of parasympathetic dominance and claims that it can be effectively used in the management of snoring.